THE SIDE PANELS TOOTH CONTACT SURFACES CARIES GENDER DIFFERENCES INCIDENCE - E. A. Bragin; A. V. Kheigetyan (Кубанский научный медицинский вестник, 2014)
This article discusses the gender differences study results up to the frequency of occurrence of the most difficult diagnosed caries process located in the area between the contacts. The men and women chewing teeth thorough inspection, using visual and tactile clinical examination and inter-proximal radiography, was conducted, that is the most accurate method at the diagnostics of teeth contact surfaces caries (CSC). Dental caries prevalence analysis for chewing teeth contact surfaces was held out, both in general and separately by teeth type (molars and premolars), on the upper and lower jaws, on the right and left sides. The trends and statistically significant lateral teeth gender frequency of occurrence differences (FOD) according to the groups of dental row, and teeth type were identified.